A generalized method for numerical modeling of seismically resilient friction dampers using flat slider bearing element. (15th January 2023) - Tatar, Arman; Baker, Alexander M.; Dowden, Daniel M.
Abstract: There has been a growing interest in recent years by both researchers and industry in developing friction dampers that have enhanced seismic performance by using inclined friction interfaces (i.e., not colinear with the plane of loading) in combination with a re-centering mechanism such as steel disc springs and/or SMA materials. These friction and friction-hybrid dampers provide both energy dissipation and self-centering characteristics. Compared to conventional flat-slider friction dampers (where friction interface is colinear with the plane of loading), numerical modeling of these types of friction devices is not straightforward and requires unique material models or complex element configurations to predict earthquake building responses. This technical note provides a generalized numerical model implemented in the OpenSees structural analyses framework that could be broadly applied to the numerical modeling of seismically resilient type friction dampers. The modeling scheme presented in this study utilizes readily available elements (i.e., flat-slider bearing element), eliminating the need and complexity of creating new material models. Given the increased interest found in the literature in the development of friction dampers with re-centering characteristics, this technical note could be useful for both researchers and engineers. Illustrative examples using two distinctly different seismically resilient friction dampers are presented for validation of the proposed modeling scheme. The first comparison is made with a cross-laminated timber rocking wall detailed with a newly proposed Uplift Friction Damper (UFD). Comparisons are made with both quasi-static cyclic tests and a continuum finite element numerical model in the ABAQUS software program. The second validation example compares results with a quasi-static uniaxial cyclic test of a Friction Spring Damper (FSD) device. Predictions of the proposed generalized numerical model are in good agreement with the results of both validation examples.